A consolidação institucional do Tribunal Superior do Trabalho (TST) na longa Constituinte (1987-2004) - Freitas, Lígia Barros de (2012)
The objective of this thesis is to analyze the political performance of the Superior Labor Court (TST) and the Legislative Power in the context of changes to the Labor Law between 1987 and 2004. To reach this objective, we analyze the internal procedure of TST, classify the institutional changes factors responsible for altering the political performance of the TST in the course of the constituent process in the Constituent Assembly (ANC) during the 1987/1988 period, as well as in the constituent reform process in the Judiciary Power Reform (which gave rise to the Constitutional Amendment 24/1999 and Constitutional Amendment 45/2004). Likewise, these aspects of institutional change generated changes in the direction of jurisprudence and the policy of judiciary organization of the TST. In the ANC of 1987/1988, the political performance of the TST, which did not represent the Labor Court, returned to the constitutional articles of its structure and expertise, and attained little public visibility. In the Judiciary Power Reform, the TST started to participate in public hearings, increasing its public visibility and legitimizing itself as an outlet to represent the Labor Court when facing other powers, as well as about human rights issues related to employment. Therefore, this research reflects the support of the legislative model of labor relations in Brazil in the institutional consolidation process of the TST.